Food as Destination: Cultural Delicacies as Motivating Factor for Tourists to Travel - Roseanne A Valino; Precil Nicole G Canoy; Marinel Pearl A Lopez; Samantha Mae C Sumang; Kenneth M Agao; Rovena I Dellova (Research Synergy Foundation Press, 2025)
What makes a destination iconic has something to do with the unique experience of the tourist, whether seeking novelty or popularity in new places. This study aimed to gain a thorough understanding of tourists’ motivating factors in choosing cultural delicacies as the basis of their travel destination. This utilized a quantitative research design using a descriptive approach. Data were gathered from 376 res9pondents using snowball sampling, and the results were analyzed using frequency distribution, weighted mean, and analysis of variance (ANOVA). The majority of the respondents are female (62%), aged 30 years and below (79.8%), and from Manila (25.5%). The findings revealed that tourists are concerned about cultural delicacies’ characteristics in taste, freshness of ingredients, and visual appearance, all labeled as